Evaluation of Thermal Stress in Saccharomyces cerevisiae Concerning Ethanol Production and Assimilation of Amino Acids in Saccharine Substrate - Santos, Maria do Socorro Mascarenhas; Mueller, Larissa Pires; Batistote, Margareth; Cardoso, Claudia Andrea Lima (Orbital: The Electronic Journal of Chemistry, 2021)
Fuel ethanol has been consolidated in view of the current energy matrix. However, for an efficient process, the yeast and the quality of the substrate used must be taken into account. Thus, this study aims to evaluate sugarcane juice and sweet sorghum and analyze cell viability, ethanol production and the assimilation of amino acids present in these substrates as a function of temperature. The Industrial yeasts Saccharomyces cerevisiae FT858 and Pedra-2 (Pe-2) were activated with pre-inoculum of 2% YPD. The biomass obtained was inoculated on the substrates and incubated at 30 and 40°C at 250 rpm. Aliquots were collected for feasibility analyses with methylene blue, ethanol by gas chromatography and amino acids by high performance liquid chromatography. Yeasts showed better performance in sorghum broth at 30°C. The viability of 89% for Pe-2 and 85% for FT858 and ethanol concentration of 10% (v v-1) for both yeasts. At 40°C there was a reduction in these parameters. Sorghum had the highest amount of amino acids and serine, arginine, alanine and tryptophan were effectively assimilated by yeasts. The temperature of 40°C interfered in the metabolic capacity of the yeasts, causing thermal stress, inducing a greater consumption of amino acids.DOI: http://dx.doi.org/10.17807/orbital.v13i4.1553